Hull-White’s value at risk model: case study of Baltic equities market - Radivojević, Nikola; Ćurčić, Nikola V.; Vukajlović, Djurdjica Dj. (Journal of Business Economics and Management, 2017)
Analysis of the applicability of the Hull and White (FHS) model on the Baltic equities market has not been the subject of significant research, especially not in the context of meeting the Basel Committee backtesting rules. The paper discusses the applicability of different variants of this model, in order to answer the question whether any variants (and which of them) of the model can be used in these markets in the context of the Basel II and III standards. The survey results show that 1) there isn’t an optimal variant of this model, but that risk managers have to keep in mind stylized facts of financial returns when they specify the FHS model; 2) according to different criteria of the validity of the model (Basel II and III standards) different variants of models are differently ranked, which suggests that selection of a suitable model implies the use of a large number of different criteria, the model validity and loss function, especially those who take care of the size of tail loss and ES.